The insurgency of the Spirit: Jesus's liberation animist spirituality, empire, and creating Christian protectors - Goss, Robert (Lexington Books, 2020)
"This book is an animist Christian liberation theology and a call to insurrection against the fossil fuel empires that have created the climate catastrophe. As such, it retrieves the animist Jesus to inspire resistance to anti-ecological, contemporary settler colonization of the Earth"--